A Comparative Study of Thanksgiving Traditions: Gotilon in Batak Culture and Erntedankfest in German Society - Marpaung , Ester Anisa Mangisi; Perdamean, Ahmad Sahat (International Journal of Education and Literature, 2025)
This study aims to analyze and compare the thanksgiving tradition of Gotilon in Batak society with the celebration of Erntedankfest in German culture. Both traditions are expressions of gratitude for the harvest and life’s blessings, yet they have developed within different cultural, social, and religious contexts. The research employs a descriptive qualitative method with a comparative-analytical approach. The findings reveal that Gotilon carries a strong religious dimension integrated with Batak customary practices, whereas Erntedankfest is more symbolic in modern German society, focusing on church services and social activities. This comparison highlights how values of gratitude are manifested through traditions shaped by cultural norms and societal development. This study is expected to enrich cross-cultural understanding and foster greater appreciation for both local and global heritage traditions.